Cost‐effectiveness analysis of primary treatments for localised prostate cancer: A population‐based Markov analysis using real‐world evidence. (14th October 2022) - Weng, Xiuhua; Zhong, Lixian; Xiang, Pin; Li, Yiyuan; Paciorek, Alan; Dong, Liangliang; Broering, Jeanette; Carroll, Peter R.; Sanda, Martin; Wilson, Leslie
Abstract: Objective: We evaluate cost‐effectiveness of primary treatments for localised prostate cancer by uniquely combining prospectively collected real‐world outcomes and costs from UCSF Cancer of Prostate Strategic Urologic Research Endeavor (CaPSURE™). Methods: Markov models assessed cost‐effectiveness of radical prostatectomy (RP), brachytherapy, electron beam radiation therapy (EBRT) and brachytherapy with EBRT by risk from US payers perspective over 8 years. Treatment costs included office visits, hospitalisation, procedures, medication and long‐term care. Patients' surveyed HRQoL were mapped into utilities. Incremental cost‐effectiveness ratios (ICERs) used cost per quality‐adjusted life years (QALYs) and willingness‐to‐pay of 150, 000/QALY. Results: Cost‐effectiveness analysis (CEA) showed for low‐risk prostate cancer, EBRT dominated the lowest cost brachytherapy, but RPns and brachytherapy plus EBRT were cost‐effective compared to brachytherapy with ICERs of 18, 926 and 41, 662 per QALY. In medium‐risk patients, RP, EBRT and brachytherapy plus EBRT all were cost‐effective compared with brachytherapy, with ICERs of 30, 604, 22, 588 and 21, 627/QALY. In high‐risk, brachytherapy dominated all treatments. Procedure cost and utility are driving ICER, but probabilistic sensitivity analysis showed the model was robust across variables. Conclusion: This first CEA combining prospective real‐world evidence for HRQOL outcomes with costs shows cost‐effectiveness of treatments vary by risk groups, providing new evidence for treatment decisions.